Theories of Knowledge: Fate and Forgetting in the Early Works of Walter Benjamin - Timothy Bahti (Studies in 20th & 21st Century Literature, 1986)
Philosophy, and the part of it devoted to epistemology or theories of knowledge, were the site of Walter Benjamin's early training and writing. Simultaneously, he turned toward a critical conception of experience and what he called the linguistic essence of knowledge. This turn manifested itself in a series of writings, all of which focused on ways in which knowledge might emerge from the reading of signs. Knowledge of fate or character, of the future or the present of persons and languages, is embedded within a theory of reading as the noting of signs qua signs. Images appear as the signs for such signs, and the problem of reading images becomes the image for a theory of reading. Through readings of selected passages from writings dating from the teens through the early thirties—principally "Fate and Character," "Oneway Street," "On the Image of Proust," and "Berlin Chronicle"—Benjamin's themes of fate and character, remembering and forgetting, are shown to display a fate of reading: the fate at once to see reading, to forget it, and to read this forgetting.
Keywords: Walter Benjamin; epistemology; theories of knowledge; experience; linguistic essence of knowledge; fate; character; qua; languages; future; present; Fate and Character; Oneway Street; On the Image of Proust; Berlin Chronicle; remembering; forgetting